2011
DOI: 10.3892/ol.2011.436
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic compounds as anticancer agents: Evaluation of synthesis and in vitro cytotoxicity

Abstract: Abstract. Polycyclic aromatic hydrocarbons (PAHs) are considered to be significant environmental carcinogens. Additionally, various planar ring systems are capable of intercalating with DNA, leading to a number of drugs that possess chemotherapeutic activity. In this study, three new polyaromatic compounds with a side chain were synthesized, and spectroscopic as well as elemental analyses were performed. The addition of the long chains to either chrysene or pyrene caused a red-shift in the spectral emission wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…As a part of our ongoing research, we have been engaged for the synthesis of new anticancer agents with special emphasis on b-lactam anticancer for the past several years. [39][40][41][42][43][44][45] We have also developed new methodologies for the synthesis of anticancer pyrroles. 33,39 During the course of investigation on Paal-Knorr synthesis of pyrroles, we envisage that 1,2,5-trisubstituted pyrroles, where position 1 (nitrogen) is substituted by b-lactam moiety can be synthesized by reacting 3-amino b-lactams and 2, 5-hexanedione as the staring materials in the presence of an acidic catalyst following Paal-Knorr method.…”
Section: Resultsmentioning
confidence: 99%
“…As a part of our ongoing research, we have been engaged for the synthesis of new anticancer agents with special emphasis on b-lactam anticancer for the past several years. [39][40][41][42][43][44][45] We have also developed new methodologies for the synthesis of anticancer pyrroles. 33,39 During the course of investigation on Paal-Knorr synthesis of pyrroles, we envisage that 1,2,5-trisubstituted pyrroles, where position 1 (nitrogen) is substituted by b-lactam moiety can be synthesized by reacting 3-amino b-lactams and 2, 5-hexanedione as the staring materials in the presence of an acidic catalyst following Paal-Knorr method.…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our research on environmentally benign reaction and biological evaluation of various polyaromatic compounds as novel anticancer agents [20-26], we have investigated reaction between aromatic amines (1) with 2,5-diemthoxytetrahydrofuran (2) using aqueous polystyrene sulfonate. After various experimentations, we have identified that this method works well under microwave-induced reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that alteration of the structure of polyaromatic compounds can help to interact with specific organelles to evoke selective cytotoxic reactions (Palmer et al, 1992; Cherubim et al, 1993). This simple, but very crucial concept is used by many scientists and as result of these approaches many carbazoles, anthracenes, and related structures are in current clinical use (Iyengar et al, 1997; Brana et al, 2001; Martinez and Chacon-Garcia, 2005; Landis-Piwowar et al, 2006; Rescifina et al, 2006; Bandyopadhyay et al, 2012). Despite huge progress in the identification of numerous active cancer chemotherapeutic agents, synthesis and biological evaluation of new methoxy dibenzofluorene derivatives has not been reported.…”
Section: Introductionmentioning
confidence: 99%